Maintaining a Bronx inpatient psychiatry service at full capacity during the COVID‐19 pandemic - Sarcevic, Nermica (Perspect Psychiatr Care, 2021)
PURPOSE: The purpose of this article is to present an overview of rapidly transformed workflows on our inpatient psychiatry service during COVID‐19 pandemic outbreak in New York. CONCLUSION: Rapidly transformed workflows, staffing patterns and discharge policies, as well as programs addressing the emotional and social needs of our staff enabled us to not only run our service without interruptions and maintain full inpatient census but also prevent the spread of COVID‐19. PRACTICE IMPLICATIONS: The challenges we faced and lessons we learned can be easily applied to other inpatient psychiatry services as we anticipate the second surge of COVID‐19 infection.